Solid desiccants from natural and modified bentonites - Castrillo, Natalia Paola (2018)
The aim of the present work was to study Argentinean natural clays with different modifications and their use as desiccants. To this end, bentonite clays collected from different regions were characterized and modified by heat treatment and calcium addition, and the desiccant capacity, in the form of powder and pellets, was studied. In addition, the hydration degree reversibility of these materials was estimated. The mineralogical and structural characterization was performed by X-ray diffraction, Fourier-transform infrared spectroscopy, differential thermal analysis, and thermogravimetric analysis. The textural characterization was performed by adsorption-desorption of N2, chemical composition by X-ray fluorescence and cation exchange capacity. The water adsorption was determined at 25 °C between 11-98% relative humidity. The results indicated that the desiccant power has a close relationship with the degree of clay purity, drying of the sample and the method of calcium incorporation.